Advancing culture of living with landslides. Volume 3, - Mikoš, Matjaž; Arbanas, Željko; Yin, Yueping; Sassa, Kyoji (Springer, 2017)
This volume contains peer-reviewed papers from the Fourth World Landslide Forum organized by the International Consortium on Landslides (ICL), the Global Promotion Committee of the International Programme on Landslides (IPL), University of Ljubljana (UL) and Geological Survey of Slovenia in Ljubljana, Slovenia from May 29 to June 2, 2017. The complete collection of papers from the Forum is published in five full-color volumes. This third volume contains the following: " One keynote lecture " Landslide Monitoring and Warning: Monitoring Techniques and Technologies, " Early Warning Systems " Landslide Disasters and Relief: Case Studies, Emergency Measures, First Aid, " Civil Protection Measures " Landslide Mitigation, Remediation and Stabilization: Landslide Protection Works, " Landslide Stabilization And Remediation Measures, Landslide Non-Structural Measures Prof. Matjaž Mikoš is the Forum Chair of the Fourth World Landslide Forum. He is the Vice President of International Consortium on Landslides and President of the Slovenian National Platform for Disaster Risk Reduction. Prof. Željko Arbanas is representative of Croatian Landslide Group, member of the International Consortium on Landslides. He is the Head of Geotechnical Chair at Faculty of Civil Engineering University of Rijeka, Croatia and the Assistant Editor-in-Chief of International Journal "Landslides".<Prof. Yueping Yin is the President of the International Consortium on Landslides and the Chairman of the Committee of Geo-Hazards Prevention of China, and the Chief Geologist of Geo-Hazard Emergency Technology, Ministry of Land and Resources, P.R. China. Prof. Kyoji Sassa is the Founding President of the International Consortium on Landslides (ICL). He is Executive Director of ICL and the Editor-in-Chief of International Journal "Landslides" since its foundation in 2004. IPL (International Programme on Landslides) is a programme of the ICL. The programme is managed by the IPL Global Promotion Committee including ICL and ICL supporting organizations, UNESCO, WMO, FAO, UNISDR, UNU, ICSU, WFEO, IUGS and IUGG. The IPL contributes to the United Nations International Strategy for Disaster Reduction and the ISDR-ICL Sendai Partnerships 2015-2025.